2010
DOI: 10.1136/ard.2009.120857
|View full text |Cite
|
Sign up to set email alerts
|

Serum branched-chain amino acid to histidine ratio: a novel metabolomic biomarker of knee osteoarthritis

Abstract: This is the first serum-based metabolomic study of osteoarthritis in humans. The branched-chain amino acids to histidine ratio has potential clinical use as an osteoarthritis biomarker and shows the clinical potential of metabolomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
5
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 24 publications
6
137
5
2
Order By: Relevance
“…We would also like to note that, while direct comparison of our results to some of the reported findings is difficult as different methods and sample types were used, we did observe an increase in the ratios of valine/histidine, leucine/histidine and isoleucine/histidine for the OA group at week 14, compared to the control group (week 14 sham group) (Supplemental Figure S12), which is consistent with the findings reported by Zhia et al . in the human samples19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We would also like to note that, while direct comparison of our results to some of the reported findings is difficult as different methods and sample types were used, we did observe an increase in the ratios of valine/histidine, leucine/histidine and isoleucine/histidine for the OA group at week 14, compared to the control group (week 14 sham group) (Supplemental Figure S12), which is consistent with the findings reported by Zhia et al . in the human samples19.…”
Section: Discussionmentioning
confidence: 99%
“…Several metabolomic profiling studies using human subjects and animal models have been reported on the investigation of metabolic responses to OA using biofluids such as urine, plasma and synovial fluids1819202122. Li et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectroscopy has also been used to look for novel biomarkers for knee OA (Zhai et al, 2010). They looked at serum samples of unrelated white women with and without knee OA.…”
Section: Osteoarthritismentioning
confidence: 99%
“…This may be due to altered permeability in inflamed tissues and thereby increased influx of fatty acids. In inflammation increased protein breakdown can be judged by the increased levels of essential amino acids as shown by the increased valine levels in patients of osteoarthritis [28]. In Crohn's disease and ulcerative colitis, analysis of fecal extracts showed decreased levels of butyrate, acetate and methylamine [29], suggesting that reduced amounts of gut bacteria may have a role to play in these diseases.…”
Section: Chronic Inflammationmentioning
confidence: 99%